The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1024/85957-000
|View full text |Cite
|
Sign up to set email alerts
|

Schluss mit dem Hintenrumgerede!

Abstract: Geschützte Warennamen (Warenzeichen) werden nicht besonders kenntlich gemacht. Aus dem Fehlen eines solchen Hinweises kann also nicht geschlossen werden, dass es sich um einen freien Warennamen handelt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…ZPD has its theoretical premises in Vygotsky's sociocultural theory which conceived of learning and human development as a fundamentally socially situated activity, embedded in a specific cultural environment (De Guerrero & Villamil, 2000). Recent empirical works have evidenced that not only experts can offer effective support, this form of supportscaffolding can also occur among peers (De Guerrero & Villamil, 2000;Saeed & Ghazali, 2017;Storch, 2019). In the peer review process, two or more students interact to provide each other with feedback on one another's written texts.…”
Section: Peer Review As Peer Scaffoldingmentioning
confidence: 99%
See 1 more Smart Citation
“…ZPD has its theoretical premises in Vygotsky's sociocultural theory which conceived of learning and human development as a fundamentally socially situated activity, embedded in a specific cultural environment (De Guerrero & Villamil, 2000). Recent empirical works have evidenced that not only experts can offer effective support, this form of supportscaffolding can also occur among peers (De Guerrero & Villamil, 2000;Saeed & Ghazali, 2017;Storch, 2019). In the peer review process, two or more students interact to provide each other with feedback on one another's written texts.…”
Section: Peer Review As Peer Scaffoldingmentioning
confidence: 99%
“…Coté's study (2014) on peer review in an English as Foreign language (EFL) class showed that students appreciated the prospect of having their written texts reviewed by their peers and the opportunity to rectify those errors in their revised version. Students are more likely to offer feedback as well as engage with the feedback provided by learning peers (Storch, 2019).…”
Section: Peer Review As Peer Scaffoldingmentioning
confidence: 99%